The Relationship Between Medication Compliance And Relapse In Schizophrenia Patients - Sukrang; Fauzan; Hasnidar; M Khariyah; MA Munir (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
Many factors can cause relapse in schizophrenia patients. Non-compliance to taking medication is one of the factors that cause relapse in schizophrenia patients. In patients with schizophrenia, noncompliance to medication is a common occurrence driven by many factors and is considered a significant contributor to relapse. This research is an observational study using a cross-sectional study design. The population in this study were the families of Schizophrenia patients who were treated in the Sawo Room, Madani Hospital, Central Sulawesi Province when the study was conducted. The sample size is 48 patients. The purposive sampling technique was used for the sampling method. The Chi-Square was used for the hypothesis test with a significance level of p < 0.05. Based on the results of the study, it was found that there was a significant relationship between medication compliance and relapse in schizophrenia patients at Madani Hospital, Central Sulawesi Province with P Value = 0.000 (< 0.05). It can be concluded that there is a relationship between medication compliance and relapse in schizophrenia patients. The hospital is expected to improve the ability of nurses to cooperate with all parties, especially families in caring for schizophrenic patients so that the recurrence of schizophrenic patients can be prevented.